Small-molecule screen in C. elegans identifies benzenesulfonamides as inhibitors of microsporidia spores - Qingyuan Huang; Haiyi Jiang; Junhong Wei; Yabin Dou; Guoqing Pan; Jie Chen; Aaron W. Reinke (npj Antimicrobials and Resistance)
Abstract Microsporidia, a large group of fungal-related intracellular parasites, infect several economically significant animals, leading to substantial economic losses. As currently available anti-microsporidia therapies are either ineffective or come with numerous adverse effects, there is a need for alternative microsporidia inhibitors. Here we screen a subset of the ChemBridge DIVERset library, comprising 2500 diverse compounds, using Caenorhabditis elegans infected with its natural microsporidian parasite, Nematocida parisii. By testing these compounds at 60 μM in 96-well assay plates, we identified 26 hits that restored the ability of C. elegans to produce progeny in the presence of N. parisii. We confirmed that out of 20 tested compounds, 18 ChemBridge compounds effectively inhibit N. parisii infection in C. elegans. Of these 18, 10 were benzenesulfonamide derivatives which inhibit microsporidia infection by inactivating spores. We screened an additional 475-compound benzenesulfonamide library, successfully identifying three compounds that are effective at a lower concentration than the initial hits. We further show that one benzenesulfonamide compound displays inhibitory activity against several species of microsporidia, inhibiting infection of species belonging to the Nematocida, Enterocytozoon, and Encephalitozoon genera. Together our results suggest that benzenesulfonamides are a potential scaffold for the development of microsporidia antiseptics.